2006
DOI: 10.1007/s00213-006-0374-7
|View full text |Cite
|
Sign up to set email alerts
|

Separable noradrenergic and dopaminergic regulation of prepulse inhibition in rats: implications for predictive validity and Tourette Syndrome

Abstract: PPI is regulated by both norepinephrine and dopamine substrates that are neurochemically separable. The PPI-protective effects of clonidine suggest that the noradrenergic regulation of PPI may have utility for predicting therapeutic benefit in TS for drugs other than antipsychotics. Clonidine's failure to prevent the PPI-disruptive effects of apomorphine or phencyclidine further support the specificity of these PPI models for detecting drugs with antipsychotic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 69 publications
(84 reference statements)
6
32
1
Order By: Relevance
“…It was found that APO (Po0.01) and DOI (Po0.01) significantly reduced PPI (vehicle values ¼ 69±3; APO ¼ 34 ± 10; DOI ¼ 48 ± 5), that the SCH23390/APO (60 ± 7) and haloperidol/APO (59 ± 8) values were significantly higher than those for the vehicle/APO condition (Po0.05), and that the ritanserin/DOI condition (68±5) was significantly higher than the vehicle/DOI (Po0.05). These results agree with previous reports indicating that the presently used doses are sufficiently high to normalize PPI deficits produced by DA or 5-HT agonists, and further confirm that the failure of DA and 5-HT receptor antagonists to reverse LC-mediated PPI deficits is not just due to underdosing with these compounds (Bakshi and Geyer, 1997;Swerdlow et al, 2006).…”
Section: Lc-mediated Ppi Disruption Is Independent Of Da or 5-ht2 Recsupporting
confidence: 92%
See 4 more Smart Citations
“…It was found that APO (Po0.01) and DOI (Po0.01) significantly reduced PPI (vehicle values ¼ 69±3; APO ¼ 34 ± 10; DOI ¼ 48 ± 5), that the SCH23390/APO (60 ± 7) and haloperidol/APO (59 ± 8) values were significantly higher than those for the vehicle/APO condition (Po0.05), and that the ritanserin/DOI condition (68±5) was significantly higher than the vehicle/DOI (Po0.05). These results agree with previous reports indicating that the presently used doses are sufficiently high to normalize PPI deficits produced by DA or 5-HT agonists, and further confirm that the failure of DA and 5-HT receptor antagonists to reverse LC-mediated PPI deficits is not just due to underdosing with these compounds (Bakshi and Geyer, 1997;Swerdlow et al, 2006).…”
Section: Lc-mediated Ppi Disruption Is Independent Of Da or 5-ht2 Recsupporting
confidence: 92%
“…Thus, the current results suggest the exciting possibility that LC-mediated PPI deficits are transduced through a novel DA-and 5-HT2-independent pathway that may operate in parallel to previously characterized substrates of PPI. The notion of parallel monoaminergic mechanisms for PPI has been suggested previously by systemic pharmacological studies using agonists and antagonists for DA and NE (Bakshi and Geyer, 1997;Carasso et al, 1998;Swerdlow et al, 2006), but the present studies for the first time implicate a specific neuroanatomical substrate in this dissociation.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations